Double-Balloon Enteroscopy following Capsule Endoscopy in the Management of Obscure Gastrointestinal Bleeding: Outcome of a Combined Approach - Patarapong Kamalaporn; Sarah Cho; Nancy Basset; Maria Cirocco; Gary May; Paul Kortan; Gabor Kandel; Norman Marcon (Canadian Journal of Gastroenterology)
BACKGROUND: There is no consensus on the relative accuracy of capsule endoscopy (CE) versus double-balloon enteroscopy (DBE) to investigate obscure gastrointestinal bleeding (GIB). CE is less invasive, but DBE more directly examines the small bowel, and allows tissue sampling plus therapeutic intervention.